BIG FIVE FACTORS PERSONALITY SEBAGAI PREDIKTOR KEPATUHAN TERHADAP PROTOKOL KESEHATAN DI MASA PANDEMI COVID-19 - Triana Wulandari; Akhmad Fauzie; Windah Riskasari (Jurnal Psikologi Poseidon, 2021)
This study aims to determine whether the dimensions of extraversion, neuroticism, openness to experience, agreeableness, and conscientiousness can predict adherence to health protocols during the Covid-19 pandemic in college students. Respondents were Hang Tuah University students as many as 362 were selected using proportionate stratified random sampling. The compliance variable has 34 valid items with a reliability value of 0.950. The Big Five Factors Personality variable has 31 valid items with a reliability value of 0.785 for the Neuroticism dimension, 0.804 for the Extraversion dimension, 0.699 for the Openness to Experience dimension, 0.590 for the Agreeableness dimension, and 0.724 for the Conscientiousness dimension. The results show that the big five personality factors can be a predictor, with a coefficient of 0.040. Other results show that extraversion cannot be a predictor of adherence to health protocols during a pandemic, while neuroticism, openness to experience, agreeableness, and conscientiousness can be predictors of adherence to health protocols during a pandemic.